Jejak Sejarah Lapangan Udara Kemayoran 1940-1985 - Muhammad Taufiq Nurwansyah (PATTINGALLOANG, 2022)
AbstractThis research aims to explain the situation of Kemayoran airfield when it was used as a military airfield from when it was first inaugurated in 1940 until its operational discontinuation in 1985. The research method used in this study is the historical method which consists of heuristics, verification, interpretation and historiography. Researchers at the heuristic stage collect both primary sources in the form of newspapers that have been published from 1935 to 1940 such as Bataviaasch Nieuwsblad and secondary sources such as books related to Kemayoran. The results of the research show that after the construction of the Kemayoran airfield which was carried out since 1934 and was completed in 1940, Kemayoran became an international aviation hub for KLM and KNILM, but since 1941 Kemayoran began to be used by VVC to train fighter pilots to prepare in case of war. When the second world war in the Pacific erupted, Kemayoran, which received several attacks from Japan, was used by the Allies as a base for fighter aircraft and also as an evacuation site. After the second world war, Kemayoran was reused by the Allies as one of the airfields that facilitated the rescue of APWI. Kemayoran was then integrated into the air defense system of the Indonesian Air Force's Kohanud, namely the Air Defense Wing 300. The history of the Kemayoran airfield began to end when the government through the Jakarta International Airport project moved flight operations to Cengkareng international airport.Key Words : Airfield, Airplane, Indonesian Air Force, Kemayoran